How prenatal environmental factors affect rat molar enamel formation - ÖZKAN YENAL, NAZİYE; MENTEŞ, ALİ RECAİ (My University, 2022)
Amelogenin (AMELX) and ameloblastin (AMBN) are crucial for enamel formation, and interruptions in the production of these proteins may cause enamel defects. We investigated how prenatal environmental factors (chronic stress, bisphenol A (BPA), amoxicillin, and lipopolysaccharide (LPS)) affect AMELX and AMBN production of ameloblasts. Fifteen pregnant Sprague-Dawley rats were divided into four experimental groups and a control group. Chronic-stress group rats were exposed to a 12:12 light/light cycle (LL) from day E18 until delivery. BPA group rats were orally administered 5 mu g/kg BPA daily from day E1 until delivery. Amoxicillin group rats were injected 100 mg/kg amoxicillin daily from day E18 until delivery. LPS-infection group rats were injected 125 mu g/kg bacterial LPS once on day E18. Seven pups from the control group and ten pups from the experimental groups were euthanized on P10. Sections were stained with hematoxylin and eosin (H&E) and Gomori\"s one-step trichrome staining (GT) and incubated with rabbit polyclonal antibodies to AMELX and AMBN, to evaluate staining intensity at ameloblast stages. The surface morphology was evaluated with a stereomicroscope. AMELX (p = 0.008, p = 0.0001, p = 0.009) and AMBN (p = 0.002, p = 0.001, p = 0.0001) staining of all groups were significantly lower than that of the control group in the secretory, transitional, and maturation stages. Abnormal enamel matrix formation was observed in the H&E and GT staining sections of all experimental groups. Yellowish coloration of the amoxicillin group was observed in morphologic evaluation.
Keywords: Tıp; Sağlık Bilimleri; Diş Hekimliği; Medicine; Health Sciences; Dentistry; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Klinik Tıp; Klinik Tıp (MED); DENTISTRY, ORAL SURGERY & MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Orthodontics; Oral Surgery; Dentistry (miscellaneous); Dental Hygiene; Periodontics; Dental Assisting; General Dentistry; Enamel; Developmental biology; Enamel formation; Extracellular matrix; Histochemistry; STRESS; AMOXICILLIN; EXPOSURE; INCISOR; AMELOBLASTIN; PREVALENCE; ETIOLOGY; DEFECTS; MATRIX; GROWTH; Enamel; Developmental biology; Enamel formation; Extracellular matrix; Histochemistry